Does Halal Tourism Development Support Achievement of SDGs Goals? A Systematic Literature Review - Ilmi, Hikmatul; Ambariyanto, Ambariyanto (Jurnal Ilmiah Ekonomi Islam, 2024)
The objective of this research is to figure out the role of halal tourism to the achievement of the Sustainable Development Goals (SDGs), in addition to identifying the factors that promote or hinder the growth of halal tourism in Indonesia. The primary data search procedure utilizes Publish or Perish software in conjunction with two databases, Google Scholar and Scopus. The outcomes of the analysis of the data comprised eight journal articles that were published between 2019 and 2023. This study's results indicate that the development of halal tourism contributes in numerous ways to the attainment of the SDGs. It can alleviate poverty in tourist destinations by generating employment opportunities for locals. Secondly, halal tourism ensures healthy and secure food and beverages. It has additionally equipped infrastructure for public facilities. Nevertheless, the growth of halal tourism in Indonesia encounters numerous impediments, among which is the absence of a comprehensive regulatory framework pertaining to this sector. Whereas, the community and business actors' consent and support for the sustainable management of halal destinations in Indonesia are the driving forces behind its development. Furthermore, these actors engage in collaborative planning and partnerships with other entities concerned with the management and advancement of tourism objects.